Biodiversity of phytoplankton in Duyen Hai town, Tra Vinh province - Trang, Le Thi; Tu, Nguyen Van; Anh, Tran Thi Lan; Thien, Luong Duc (Vietnam Journal of Marine Science and Technology, 2020)
This study was conducted to enhance the understanding of phytoplankton diversity of Duyen Hai town, Tra Vinh province. We selected 12 representative sampling sites and investigated phytoplankton diversity in both dry and rainy seasons. The phytoplankton of this area were comprised of 134 species, belonging to 64 genera, 45 families, 31 orders, 8 classes and 5 divisions. Among those divisions, Bacillariophyta was the most dominant in species, accounting for 70% of the total number of species and Cyanobacteria commonly had high density at 12 surveyed sites. The average density of phytoplankton was 1,195 cells/l in the rainy season and 2,020 cells/l in the dry season, respectively. For water bodies with the exchange of freshwater and marine water, the diversity is typically higher than in water bodies with purely freshwater or marine conditions